2003
DOI: 10.1603/0022-2585-40.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria in Midguts of Field-Collected <I>Anopheles albimanus</I> Block <I>Plasmodium vivax</I> Sporogonic Development

Abstract: Bacterial infections were investigated in midguts of insectary and field-collected Anopheles albimanus Weidemann from southern Mexico. Serratia marcescens, Enterobacter cloacae and Enterobacter amnigenus 2, Enterobacter sp., and Serratia sp. were isolated in field samples obtained in 1998, but only Enterobacter sp. was recovered in field samples of 1997 and no bacteria were isolated from insectary specimens. These bacteria were offered along with Plasmodium vivax infected blood to aseptic insectary An. albiman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
193
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(214 citation statements)
references
References 11 publications
13
193
2
4
Order By: Relevance
“…Similar to the gut microbiota of mammals, the microbiota associated with arthropods plays an important role in host development, pathogen resistance, nutrition, and physiology (69). Microbial symbionts can reduce vector competence, and specific gut microbiota play a protective role in Anopheles mosquitoes against Plasmodium colonization (70)(71)(72)(73). Although knowledge about the function of microbiota in diverse arthropods is still limited, cross-talk between the arthropod, its gut microbiota, and incoming pathogens is likely to be important (9)(10)(11)69).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the gut microbiota of mammals, the microbiota associated with arthropods plays an important role in host development, pathogen resistance, nutrition, and physiology (69). Microbial symbionts can reduce vector competence, and specific gut microbiota play a protective role in Anopheles mosquitoes against Plasmodium colonization (70)(71)(72)(73). Although knowledge about the function of microbiota in diverse arthropods is still limited, cross-talk between the arthropod, its gut microbiota, and incoming pathogens is likely to be important (9)(10)(11)69).…”
Section: Discussionmentioning
confidence: 99%
“…Others are stable residents or transients and are lost during digestion or insect moulting (Endris et al 1982, Gonzalez-Ceron et al 2003. The origin and ecological association of the midgut bacteria and the insect host is diffi cult to defi ne.…”
Section: Discussionmentioning
confidence: 99%
“…Iverson et al (1984) reported the presence of Serratia liquefaciens and S. marcescens in all sugar beet root maggot (Diptera: Oititidae) developmental stages, suggesting a symbiosis and a nutritional interdependence between these bacteria and the insect. Gonzalez-Ceron et al (2003) studied the microorganisms present in the midguts of An. albimanus and identified several Serratia and Enterobacter species including S. marcescens, E. cloacae, and E. amnigenus.…”
Section: Discussionmentioning
confidence: 99%
“…Some works have already reported the isolation of microorganisms from the midgut of Culex quinquefasciatus, Anopheles dirus, Anopheles albimanus, and Ae. aegypti , Khampang et al 1999, Luxananil et al 2001, Pidiyar et al 2002, Gonzalez-Ceron et al 2003. The microbiota of Anopheles gambiae and Anopheles funestus was also investigated by 16S rDNA sequence by Lindh et al (2005).…”
Section: We Show For the First Time That The Ventral Diverticulum Of mentioning
confidence: 99%